"CO-OPERATIVE BANK EMPLOYEES PERFORMANCE APPRAISAL OF SOLAPUR DISTRICT" - Ms. Archana V. Gaur, Dr. Shendge Rajendra N. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Performance appraisal plays very important role for the growth and development of organisation as well as to the employees. There are many tools by which appraisal of employee are carried out. The purpose of this study is to understand the approach adopted for employee performance appraisal by the co-operative bank and its effectiveness. A questionnaire is prepared and survey is conducted of co-operative bank employees in Solapur district, Maharashtra. One of the most commonly used tools for assessing the importance of employee success is performance evaluation. The theoretical framework and model will help in making development and improvement plans and reaching agreement about what should be done in the future to enhance the banks effect and effectiveness.